The role of affective temperaments in self-care and medication adherence among individuals with bipolar disorder: a moderation analysis - Visalli, Giulia; Longobardi, Grazia; Iazzolino, Anna Maria; D’Angelo, Martina; Stefano, Valeria Di; Paribello, Pasquale; Steardo, Luca; Manchia, Mirko; Steardo, Luca (Frontiers in Psychiatry, 2024)
Background: Affective temperament, defined as the fundamental predisposition from which normal affective states originate or as the constitutional core of personality, play a crucial role in mood disorders, particularly bipolar disorders. Understanding the relationship between temperaments, treatment adherence, and self-care is crucial for effective management and improved clinical results.Objectives: This study aims to (1) assess the correlation between affective temperaments and treatment adherence, (2) investigate the relationship between affective temperaments and self-care abilities, (3) identify predictors of treatment adherence, and (4) explore the moderating effect of self-care on the relationship between treatment adherence and depressive temperament in individuals with bipolar disorder.A cross-sectional study was conducted with 231 individuals diagnosed with bipolar disorder (BD) type I (N=160) and type II (N=71). The participants were evaluated using the following psychometric tools: Temperament Evaluation of Memphis, Pisa, and San Diego (TEMPS) to assess affective temperaments, Personal and Social Performance Scale (PSP) to evaluate social functioning and self-care abilities, and Morisky Medication Adherence Scale (MMAS) to measure treatment adherence. The study involved statistical analyses to examine correlations, identify predictors, and explore moderating effects. The findings revealed significant correlations between affective temperaments and both treatment adherence and self-care abilities. Specifically, hyperthymic temperament was positively associated with higher treatment adherence, whereas cyclothymic and depressive temperaments were linked to lower adherence. Self-care abilities were found to mediate the relationship between depressive temperament and treatment adherence, suggesting that improved self-care can enhance adherence in individuals with depressive temperament.Affective temperaments significantly influence treatment adherence and self-care abilities in individuals with bipolar disorder. The mediating role of self-care highlights the importance of developing targeted interventions to improve self-care practices, thereby enhancing treatment adherence and overall well-being. Personalized treatment strategies based on temperament assessments could lead to better clinical outcomes and quality of life for individuals with bipolar disorder.